Management and outcome of epistaxis under direct oral anticoagulants: a comparison with warfarin. Issue 1 (3rd October 2018) - Send, Thorsten; Bertlich, Mattis; Horlbeck, Fritz; Schafigh, Darius; Freytag, Saskia; Eichhorn, Klaus W.; Gräff, Ingo; Bootz, Friedrich; Jakob, Mark
Abstract : Background: Epistaxis is one of the more common reasons for emergency room visits. The main risk factor for epistaxis is anticoagulant therapy. Until recently, the main culprit was oral intake of a vitamin K antagonist, such as warfarin, which has a number of side effects. Even more recently, several direct oral anticoagulants, rivaroxaban and dabigatran, have been approved for use. We investigated the possible differences between treatment of epistaxis with direct oral anticoagulants and vitamin K antagonists. Methods: We conducted a retrospective cohort study at a tertiary referral center in Germany. All patients who were admitted within a 1‐year period were included. Patient files were used to obtain the information. Results: Overall, 677 patients were included in our study. Of these, 159 had been treated with vitamin K antagonists and 49 with direct oral anticoagulants. There were no significant differences in terms of age ( p = 0.592), sex ( p = 0.372), vital signs, bloodwork, or location of bleeding ( p = 0.372). Management of epistaxis between the groups was also comparable ( p = 0.399), with similar hospital admission rates (37.1% vs 24.5%; p = 0.145) and duration of stay (3.5 ± 2.1 days vs 3.8 ± 3.3 days; p = 0.650). Conclusion: We found no evidence to suggest epistaxis is more severe or requires more invasive therapy in patients given direct oral anticoagulants. A significant proportion of patients on vitamin K antagonists were not within the target range for international normalized ratio, highlighting one of the main issues with oral anticoagulation by vitamin K antagonists.